Lost boys of Sudan : an American story of the refugee experience an American story of the refugee experience - Bixler, Mark, 1970- (Athens : University of Georgia Press, 2006)
In 2000 the United States began accepting 3,800 refugees from one of Africa's longest civil wars. They were just some of the thousands of young men, known as "Lost Boys," who had been orphaned or otherwise separated from their families in the chaos of a brutal conflict that has ravaged their home country of Sudan since 1983. [This book] focuses on four of these refugees. Theirs, however, is a typical story, one that repeated itself wherever the Lost Boys were found across America. It is a story of the countless challenges of "making it" in a strange new place after years on the run in Sudan or in refugee camps in Kenya and Ethiopia ... As we immerse ourselves in the Lost Boys' daily lives, we also get to know the social services professionals and volunteers, celebrities, community leaders, and others who guided them - with occasional detours - toward self-sufficiency. Along the way, [the author] looks closely at the ins and outs of U.S. refugee policy, the politics of international aid, the history of Sudan, and the radical Islamist underpinnings of its government.-Dust jacket.
Landing -- Bread in the dishwasher -- The spoiling of the world -- A bitter wind -- Selective compassion -- The level of responsible people -- Are y'all resettling any of these guys? -- Body language in the workplace -- September 11, 2001 -- Chasing the wind -- Can you name your sisters? -- This is your future -- Driving -- Don't get obsessed -- Peace? -- Gentlemen of the future -- Epilogue, January 2006.
Includes bibliographical references (p. 253-254) and index.
Keywords: Refugees -- Sudan; Refugees -- Georgia -- Atlanta; Orphans -- Sudan; War